Pakaian Adat Bundo Kanduang : Simbol Identitas dan Warisan Budaya Minangkabau - Lula Najwa Kamila; Syairul Bahar; Divani Truna Wijayanti; Nurazizah Nurazizah; Canggih Tri Satria; Muhammad Rizki Fadhilah; Farkhan Abdurochim Alfaruq (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
Bundo Kanduang traditional clothing is one of the important symbols in West Sumatra's cultural heritage, especially among the Minangkabau people. In addition to serving as a body covering, this garment symbolizes social status and a strong ethnic identity. This study aims to document and analyze the characteristics and social significance of Bundo Kanduang traditional clothing in the context of Minangkabau culture. The method used in this study is qualitative, which includes literature studies and interviews with the manager of the West Sumatra pavilion at Taman Mini Indonesia Indah (TMII), East Jakarta. Data was collected through direct observation during visits to the platform, as well as analysis of written sources regarding traditional Minangkabau clothing. The results of the study show that Bundo Kanduang clothing has striking characteristics, such as a headdress that resembles a buffalo horn, which symbolizes the strength and dignity of women in the Minangkabau community. This clothing also reflects the cultural values and traditions that are upheld by the local community. The implications of this study are very significant for cultural preservation. This finding can be used as a reference for cultural education in schools and as research material for future researchers. In addition, a deeper understanding of Bundo Kanduang traditional clothing can encourage people to better appreciate and preserve their cultural heritage.